Operationalizing Energy Democracy: Challenges and Opportunities in Vermont's Renewable Energy Transformation - Stephens, Jennie C.; Burke, Matthew J.; Gibian, Brock; Jordi, Elie; Watts, Richard (Frontiers in Communication, 2018)
As the social movement promoting “energy democracy” expands, analysis of how the principles of energy democracy are being operationalized is increasingly valuable. The state of Vermont provides a unique case of a United States jurisdiction intentionally promoting multiple ideals of energy democracy as the state commits to transitioning toward renewable energy. This research explores how energy democracy principles are being operationalized in the state of Vermont. Collaboration among stakeholders state-wide has resulted in a variety of social innovations that advance energy democracy goals, yet there are limited examples of community ownership and strong community opposition to some renewable projects. A diverse set of stakeholders in this small state has developed and promoted the adoption of a comprehensive energy plan with a goal of achieving 90% renewables in all sectors (electricity, heating, and transportation) by 2050. These stakeholders are aligned toward achieving this goal, and a socially innovative, networked effort seeks to establish a creative and inclusive environment for individuals, communities and organizations to benefit in the renewable energy transformation. A collaborative culture has created a protected environment where social innovation and experimentation are supported and encouraged, yet tension and community opposition surrounds some wind and solar projects. Reviewing social innovations in Vermont highlights challenges and opportunities of operationalizing energy democracy and emphasizes the importance of local community and public ownership to distribute the economic and political power associated with renewable energy.